A rare case report on linezolid induced fixed drug eruption - Prathap, T. Amul; Lokeshvaran, D.; Abinish, D. G.; Kalaivani, S.; Aswin, J. (International Journal of Research in Dermatology, 2025)
Fixed drug eruption is a rare but significant adverse drug reaction characterized by recurrent, well-defined skin lesions that consistently reappear at the same anatomical sites upon re-exposure to the offending drug. This case report presents a 48-year-old female who developed hyperpigmented patches on her left thigh and axilla followed by the administration of linezolid, an antibiotic used for treating resistant gram-positive bacterial infections. Although Linezolid is generally well-tolerated, it can cause cutaneous reactions, with fixed drug eruptions being an exceedingly rare occurrence. The patient’s condition improved significantly after discontinuation of linezolid and treatment with corticosteroids, antihistamines, and topical agents. This case underscores the importance for clinicians to consider FDE in the differential diagnosis of patients receiving linezolid, particularly when lesions appear in atypical locations such as the thigh and axilla. Additionally, it emphasizes the critical role of prompt drug cessation and appropriate symptomatic treatment in managing such adverse reactions, thereby improving patient outcomes and ensuring better clinical management.